1999
DOI: 10.1074/jbc.274.11.7226
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase Cross-linking Properties of the Small Proline-rich 1 Family of Cornified Cell Envelope Proteins

Abstract: Small proline-rich 1 (SPR1) proteins are important for barrier function in stratified squamous epithelia. To explore their properties, we expressed in bacteria a recombinant human SPR1 protein and isolated native SPR1 proteins from cultured mouse keratinocytes. By circular dichroism, they possess no ␣ or ␤ structure but have some organized structure associated with their central peptide repeat domain. The transglutaminase (TGase) 1 and 3 enzymes use the SPR1 proteins as complete substrates in vitro but in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 53 publications
2
80
1
Order By: Relevance
“…Interestingly different residues on the amino termini are used by the two enzymes, indicating that both enzymes are also required for the appropriate assimilation of SPRs into the CE in vivo. In addition, double cross-linking experiments have shown that the TGase 3 enzyme first cross-links the SPRs into short oligomers, which are later affixed to the CE by the TGase 1 enzyme (Candi et al, 1999). We have noted a correlation between the amount of SPRs present in CEs and the presumed requirements of epithelia for resistance to physical trauma.…”
Section: Structural Protein Components Of Cesmentioning
confidence: 83%
See 2 more Smart Citations
“…Interestingly different residues on the amino termini are used by the two enzymes, indicating that both enzymes are also required for the appropriate assimilation of SPRs into the CE in vivo. In addition, double cross-linking experiments have shown that the TGase 3 enzyme first cross-links the SPRs into short oligomers, which are later affixed to the CE by the TGase 1 enzyme (Candi et al, 1999). We have noted a correlation between the amount of SPRs present in CEs and the presumed requirements of epithelia for resistance to physical trauma.…”
Section: Structural Protein Components Of Cesmentioning
confidence: 83%
“…Seven members of the TGase family have been identified in the human genome so far, which are listed in Table 1. Four of these, TGases 1, 2, 3 and ✕ are commonly expressed in epithelia such as the epidermis (Kim et al , 1991;Aeschlimann et al, 1998), although to date only TGases 1 and 3 have proven importance in CE assembly (Candi et al, 1995;Tarcsa et al, 1997;Tarcsa et al, 1998Candi et al, 1999. It has also been proposed that the cross-linking by these enzymes coordinates mechanically the association between the CE and the underlying intracellular keratin intermediate filaments , and perhaps also in the bundling of keratin filaments (Clement et al, 1998).…”
Section: The Tgasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, TGases recognize the generic sequence motif Gln-Gln*-Val for the first step of the reaction (where Gln* represents the targeted residue), although different isoforms display specificity as to which substrates bearing the motif may approach the enzyme . Anecdotal data suggest less specificity for Lys substrates (Tarcsa et al, 1998;Candi et al, 1999;.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, TGases recognize the generic sequence motif Gln-Gln*-Val for the first step of the reaction (where Gln* represents the targeted residue), although different isoforms display specificity as to which substrates bearing the motif may approach the enzyme . Anecdotal data suggest less specificity for Lys substrates (Tarcsa et al, 1998;Candi et al, 1999;.The three dimensional structures of four TGases have now been reported, i.e. human factor XIIIa (hfXIIIa) ), TGase 2 (Liu et al, 2002, TGase 3 enzymes (Ahvazi et al, 2002;2003), and a fish enzyme (fTG, equivalent to mammalian TGase 2, Noguchi et al, 2001).…”
mentioning
confidence: 99%